BODIPY decorated dendrimeric cyclotriphosphazene photosensitizers: synthesis and efficient singlet oxygen generators. Issue 53 (13th May 2016) - Eçik, Esra Tanrıverdi; Şenkuytu, Elif; Cebesoy, Zeynep; Çiftçi, Gönül Yenilmez
Abstract : BODIPY decorated dendrimeric cyclotriphosphazenes were synthesized. The singlet oxygen generation capabilities of them were evaluated. They are proposed as potential photosensitizers that can be used as efficient singlet oxygen generators. Abstract : In the present work, syntheses of BODIPY decorated dendrimeric cyclotriphosphazenes (8–10 ) are described. The newly synthesized dendrimeric cyclotriphosphazenes have been characterized by 1 H, 13 C, 31 P NMR spectroscopies, and UV-Vis electronic absorption spectra. These derivatives show absorption in the NIR region with good molar extinction coefficients. Singlet oxygen generation capacities of novel compounds (8–10 ) are measured using the trap molecule 1, 3-diphenylisobenzofuran. BODIPY decorated dendrimeric cyclotriphosphazenes (8–10 ) demonstrate high singlet oxygen quantum yields. Also, each of them shows chemical and photostability under the conditions of singlet oxygen measurement. The dendrimeric cyclotriphosphazenes are proposed as potential photosensitizers that can be used as efficient singlet oxygen generators.